Micro-injection molded, poly(vinyl alcohol)-calcium salt templates for precise customization of 3D hydrogel internal architecture. (1st September 2019) - McNulty, Jason D.; Marti-Figueroa, Carlos; Seipel, Frank; Plantz, Joshua Z.; Ellingham, Thomas; Duddleston, Lukas J.L.; Goris, Sebastian; Cox, Benjamin L.; Osswald, Tim A.; Turng, Lih-Sheng; Ashton, Randolph S.
Graphical abstract: Illustration of PVOH and calcium salt compounding followed by injection molding of a sacrificial PVOH-Ca template, which is subsequently encapsulated and dissolved within an alginate hydrogel monolith. Release of calcium ions at the hydrogel-template interface enhances interior lumen molding fidelity. The resulting engineered hydrogel can then be used to mold the microscale morphology of hPSC-derived cell aggregates/organoids. Abstract: In tissue engineering applications, sacrificial molding of hydrogel monoliths is a versatile technique for creating 3D molds to control tissue morphology. Previous sacrificial templates fabricated by serial processes such as solvent casting and thermal extrusion/fiber drawing can be used to effectively mold internal geometries within rapidly polymerizing, bulk curing hydrogels. However, they display poorer performance in controlling the geometry of diffusion limited, ionically cross-linked hydrogels, such as alginate. Here, we describe the use of poly(vinyl alcohol)-calcium salt templates (PVOH-Ca) fabricated by micro-injection molding, a parallel mass-production process, to conveniently cast internal geometries within both bulk curing hydrogels and ionically cross-linked alginate hydrogels. Calcium salt solubility was discovered to be a critical factor in optimizing the polymer composite's manufacturability, mechanical properties, and the quantity of calcium released upon template dissolution. Metrological and computed tomography (CT) analysis showed that the template's calcium release enables precise casting of microscale channel geometries within alginate hydrogels (6.4 ± 7.2% average error). Assembly of modular PVOH-Ca templates to mold 3D channel networks within alginate hydrogels is presented to demonstrate engineering scalability. Moreover, the platform is used to create hydrogel molds for engineering human embryonic stem cell (hESC)-derived neuroepithelial organoids of a microscale, biomimetic cylindrical morphology. Thus, injection molded PVOH-Ca templates facilitate customization of hydrogel sacrificial molding, which can be used to generate 3D hydrogels with complex internal microscale architecture for diverse tissue engineering applications. Statement of Significance: Sacrificial molding of hydrogel monoliths is a versatile technique for creating 3D molds for tissue engineering applications. Previous sacrificial materials fabricated by serial processes have been used to effectively mold internal geometries within rapidly polymerizing, bulk curing hydrogels. However, they display poor performance in molding geometry within diffusion limited, ionically cross-linked hydrogels, e.g. alginate. We describe the use of poly(vinyl alcohol)-calcium salt templates (PVOH-Ca) fabricated by micro-injection molding, an unparalleled mass-production process, to conveniently cast internal geometries within both bulk curing hydrogels and ionically cross-linked alginate hydrogels. Calcium release from the PVOH-Ca templates enables precise sacrificial molding of alginate hydrogels and the process is biocompatible. Moreover, we demonstrate its use to engineer the morphology of hPSC-derived neuroepithelial organoids, and modular PVOH-Ca template designs can be assembled to enable scalable 3D customization of hydrogel internal architecture.